La Passion de Théodora et Didyme: Édition des traductions latines BHL 8072 et 8073 - Lanéry, Cécile (Analecta Bollandiana, 2004)
The story of Theodora and Didymus known to and used by Eusebius of Emesa and Ambrose of Milan describes the adventurous escape of a Christian virgin from the brothel to which she had been sent for refusing to sacrifice to the gods. Already in Antiquity there were two independent Latin translations, one a literal one (BHL 8072), the other a free one (BHL 8073). The translations which are here edited in parallel were made from Greek texts which were perhaps related and were fairly close to the only surviving Greek recension (BHG 1742).